Potensi Unggulan Komoditas Pertanian pada Daerah Dataran Tinggi Kabupaten Pegunungan Arfak, Papua Barat - Meky Sagrim; Agus Irianto Sumule; Deny Anjelus Iyai; Michael Baransano (Jurnal Ilmu Pertanian Indonesia, 2017)
New autonomy status of Arfak Mountains Regency has numbers of strategic potencies for being developed. The one is agriculture sector. The objective of this research was to investigate featured potency and its distribution of agricultural products in Arfak Mountains Regency. A field research was done in the year 2015 between November-December. Sampled respondents using questionnaire were interviewed. The finding of this research was that agriculture sector contributed to gross domestic regional was 72.6%. The value of Location of Quotient for horticulture sector contributed by field paddy in Minyambouw District was 2.76 similar to crop production in Sururey, Anggi, Taige, Catubouw, Testega, Donohue, Anggigida, and Hingk Districts. Mays commodity is grown in Member and Minyambouw. Districts having a majority of Location Quotient more than that >1.00 were in Minyambouw, Hingk, and Anggigida with 5 commodities. The higher Location Quotient value was presented in horticulture plants, i.e. 5.87. The Potency of households and labor resources was in the district of Minyambouw and Hingk District In general, Pegaf Regency has agriculture potency of crops, i.e. field paddy, mays, and crops.